Algorithmic justice: algorithms and big data in criminal justice settings - Završnik, Aleš (European journal of criminology, 2021)
The article focuses on big data, algorithmic analytics and machine learning in criminal justice settings, where mathematics is offering a new language for understanding and responding to crime. It shows how these new tools are blurring contemporary regulatory boundaries, undercutting the safeguards built into regulatory regimes, and abolishing subjectivity and case-specific narratives. After presenting the context for ‘algorithmic justice’ and existing research, the article shows how specific uses of big data and algorithms change knowledge production regarding crime. It then examines how a specific understanding of crime and acting upon such knowledge violates established criminal procedure rules. It concludes with a discussion of the socio-political context of algorithmic justice.